(untitled) (Global Journal of Management and Business Research, 2023)
This research portrays the epistemological bases on which qualitative studies in marketing are based In the meantime the main objective was to analyze how qualitative research published in the Revista Brasileira de Marketing is constructed based on conventional and unconventional epistemologies The methodological design was that of documentary research with content analysis The under-standing and interpretation of the articles as well as the critical evaluation carried out allow inferring that qualitative studies in marketing have a strong emphasis on the conventional basis and have positivism and the empiricist-systemic-functionalist approach as their central assumption Furthermore the influence of unconventional epistemological bases in two articles signals the emergence of critically oriented studies Even so they are approximations flirtations rather than critical studies per se because they do not widely appropriate the general categories that characterize guide and found the critical theoretical-methodological scheme